MODAL SHIFT A FLAVIA (Perner's Contacts, 2011)
The paper deals with other contexts of author’s dissertation thesis. Specifically, a calculation of the financial subsidy that the operator could get from the Operational program Marco Polo II and synergic effects with the project FLAVIA.
Keywords: calculation; modal shift; combined transport